Rearrangement of the Protein Phosphatase 1 Interactome During Heart Failure Progression. Issue 15 (9th October 2018) - Chiang, David Y.; Alsina, Katherina M.; Corradini, Eleonora; Fitzpatrick, Martin; Ni, Li; Lahiri, Satadru K.; Reynolds, Julia O.; Pan, Xiaolu; Scott, Larry; Heck, Albert J.R.; Wehrens, Xander H.T.
Abstract : Background: Heart failure (HF) is a complex disease with a rising prevalence despite advances in treatment. Protein phosphatase 1 (PP1) has long been implicated in HF pathogenesis, but its exact role is both unclear and controversial. Most previous studies measured only the PP1 catalytic subunit (PP1c) without investigating its diverse set of interactors, which confer localization and substrate specificity to the holoenzyme. In this study, we define the PP1 interactome in cardiac tissue and test the hypothesis that this interactome becomes rearranged during HF progression at the level of specific PP1c interactors. Methods: Mice were subjected to transverse aortic constriction and grouped on the basis of ejection fraction into sham, hypertrophy, moderate HF (ejection fraction, 30%–40%), and severe HF (ejection fraction <30%). Cardiac lysates were subjected to affinity purification with anti-PP1c antibodies followed by high-resolution mass spectrometry. PP1 regulatory subunit 7 (Ppp1r7) was knocked down in mouse cardiomyocytes and HeLa cells with adeno-associated virus serotype 9 and siRNA, respectively. Calcium imaging was performed on isolated ventricular myocytes. Results: Seventy-one and 98 PP1c interactors were quantified from mouse cardiac and HeLa lysates, respectively, including many novel interactors and protein complexes. This represents the largest reproducible PP1 interactome data set ever captured from any tissue, including both primary and secondary/tertiary interactors. Nine PP1c interactors with changes in their binding to PP1c were strongly associated with HF progression, including 2 known (Ppp1r7 and Ppp1r18) and 7 novel interactors. Within the entire cardiac PP1 interactome, Ppp1r7 had the highest binding to PP1c. Cardiac-specific knockdown in mice led to cardiac dysfunction and disruption of calcium release from the sarcoplasmic reticulum. Conclusions: PP1 is best studied at the level of its interactome, which undergoes significant rearrangement during HF progression. The 9 key interactors that are associated with HF progression may represent potential targets in HF therapy. In particular, Ppp1r7 may play a central role in regulating the PP1 interactome by acting as a competitive molecular "sponge" of PP1c. Abstract : Supplemental Digital Content is available in the text.